EARTH-BASED MATERIALS FOR ADDITIVE MANUFACTURING IN CONSTRUCTION: A SELECTIVE REVIEW OF MIX DESIGN - Масляненко, Євген; Хлицов, Микола (SWorldJournal, 2025)
A selective review of the up-to-date research on the additive manufacturing (AM) in construction - 3D printing technology from the earth-based materials perspective. Ways of tailoring effective mix design for the in-situ printing process using local mate